Visible light photocatalysis in organic chemistry - Stephenson, Corey; Yoon, Tehshik; MacMillan, David W. C. (Wiley-VCH Verlag GmbH & Co., 2018)
Filling the need for a ready reference that reflects the vast developments in this field, this book presents everything from fundamentals, applications, various reaction types, and technical applications. Edited by rising stars in the scientific community, the text focuses solely on visible light photocatalysis in the context of organic chemistry. This primarily entails photo-induced electron transfer and energy transfer chemistry sensitized by polypyridyl complexes, yet also includes the use of organic dyes and heterogeneous catalysts. A valuable resource to the synthetic organic community, polymer and medicinal chemists, as well as industry professionals.